VMP (Bortezomib, melphalan, and prednisone) is active and well tolerated in newly diagnosed patients with multiple myeloma with moderately impaired renal function, and results in reversal of renal impairment: Cohort analysis of the phase III VISTA study - Dimopoulos, M.A.; Richardson, P.G.; Schlag, R.; Khuageva, N.K.; Shpilberg, O.; Kastritis, E.; Kropff, M.; Petrucci, M.T.; Delforge, M.; Alexeeva, J.; Schots, R.; Masszi, T.; et al. (Journal of Clinical Oncology, 2009)
Purpose: To assess bortezomib plus melphalan and prednisone (VMP) and melphalan and prednisone (MP) in previously untreated patients with multiple myeloma (MM) with renal impairment enrolled on the phase III VISTA study, and to evaluate renal impairment reversibility. Patients and Methods: Patients received nine 6-week cycles of VMP (bortezomib 1.3 mg/m2, melphalan 9 mg/m2, prednisone 60 mg/m2) or MP. Patients with serum creatinine higher than 2 mg/dL were excluded. Results: In the VMP/MP arms, 6%/4%, 27%/30%, and 67%/66% of patients had baseline glomerular filtration rate (GFR) of ≤ 30, 31 to 50, and higher than 50 mL/min, respectively. Response rates were higher and time to progression (TTP) and overall survival (OS) longer with VMP versus MP across renal cohorts. Response rates with VMP and TTP in both arms did not appear significantly different between patients with GFR ≤ 50 or higher than 50 mL/min; OS appeared somewhat longer in patients with normal renal function in both arms. Renal impairment reversal (baseline GFR < 50 improving to > 60 mL/min) was seen in 49 (44%) of 111 patients receiving VMP versus 40 (34%) of 116 patients receiving MP. By multivariate analysis, younger age (< 75 years; P = .006) and less severe impairment (GFR ≥ 30 mL/min; P = .027) were associated with higher reversal rates. In addition, treatment with VMP approached significance (P = .07). In both arms, rates of grade 4 and 5 adverse events (AEs) and serious AEs appeared higher in patients with renal impairment; with VMP, rates of discontinuations/bortezomib dose reductions due to AEs did not appear affected. Conclusion: VMP is a feasible, active, and well-tolerated treatment option for previously untreated patients with MM with moderate renal impairment, resulting in 44% renal impairment reversal. © 2009 by American Society of Clinical Oncology.